Karakteristik Sosial Demografi yang Memengaruhi Kesejahteraan Rumah Tangga dengan Kepala Rumah Tangga Lulusan SMA Berdasarkan Kelompok Daerah di Indonesia Tahun 2020 - Mutia Fitri Octaviani; Anugerah Karta Monika (Politeknik Statistika STIS, 2022)
One of the efforts is by improving the quality of education in Indonesia. Some provinces have a high level of education but are not followed by good welfare. Therefore, this study will classify provinces based on educational indicators and welfare status. The purpose of the classification is to map factors that affect the welfare status of each regional group. This study uses Susenas raw data March 2020 and the analysis methods are descriptive analysis, quadrant analysis and binary logistic regression analysis. The result of this study is that the provinces in Indonesia are classified into four quadrants with the provinces that have the best characteristics labeled quadrant I and the provinces with the worst characteristics labeled quadrant IV. The number of household members, the age of the head of the household, the gender of the head of the household, the classification of the village / village of residence, the business field of the head of the household and the main employment status of the head of the household have a significant effect on welfare in the four quadrants.